Atomic pair distribution function at the Brazilian Synchrotron Light Laboratory: Application to the Pb1-xLaxZr0.40Ti0.60O3 ferroelectric system - Saleta, M. E. (2017)
This work reports the setting up of the X-ray diffraction and spectroscopy beamline at the Brazilian Synchrotron Light Laboratory for performing total scattering experiments to be analyzed by atomic pair distribution function (PDF) studies. The results of a PDF refinement for Al2O3 standard are presented and compared with data acquired at a beamline of the Advanced Photon Source, where it is common to perform this type of experiment. A preliminary characterization of the Pb1-xLaxZr0.40Ti0.60O3 ferroelectric system, with x = 0.11, 0.12 and 0.15, is also shown.A setup for total scattering experiments at the multi-purpose XDS beamline of the Brazilian Synchrotron Light Laboratory (LNLS) is described. Also, a preliminary characterization of the Pb1-xLaxZr0.40Ti0.60O3 (x = 0.11, 0.12 and 0.15) ferroelectric system using pair distribution function analysis is presented.